2015
DOI: 10.5539/ies.v8n12p1
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Entrepreneurial Profile: Case Study

Abstract: This article was prepared in order to investigate whether the teachers working in a Business Administration BA degree have an entrepreneurial profile, with the aim of finding whether such teachers are able to support the Pedagogical Proposal of the Institution to which they belong to in what concerns the requirement of the course and also the Pedagogical Proposal of the course itself. The methodological procedure adopted was the Documentary Analysis, i.e., a study that is based on documents such as books, stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Further, Wu et al (2018) suggested that information and communication technology can be used to enhance the effectiveness of traditional teaching methods and competency training in EE. An increasing number of scholars are using competency theory to study universities and teachers, for example, using the teacher competency training system to improve competency for education for sustainable development (Weng et al, 2020) and developing a competency-based framework for teachers' entrepreneurial behavior (Van Dam et al, 2010), teachers' entrepreneurial competencies (Peltonen, 2015;Stettiner et al, 2015), the capacity building of teachers of innovation and EE in universities (Trauth et al, 2015), and research on teacher competency and instructional quality (Blömeke et al, 2020).…”
Section: Literature Review Research On Competency Theorymentioning
confidence: 99%
“…Further, Wu et al (2018) suggested that information and communication technology can be used to enhance the effectiveness of traditional teaching methods and competency training in EE. An increasing number of scholars are using competency theory to study universities and teachers, for example, using the teacher competency training system to improve competency for education for sustainable development (Weng et al, 2020) and developing a competency-based framework for teachers' entrepreneurial behavior (Van Dam et al, 2010), teachers' entrepreneurial competencies (Peltonen, 2015;Stettiner et al, 2015), the capacity building of teachers of innovation and EE in universities (Trauth et al, 2015), and research on teacher competency and instructional quality (Blömeke et al, 2020).…”
Section: Literature Review Research On Competency Theorymentioning
confidence: 99%